Principles of foundation engineering - Das, Braja M. (Cengage Learning, 2016)
Helps you master the fundamental concepts and applications of foundation analysis design. This text offers worked out examples and figures that show you how to do the work you will be doing as a civil engineer, and helps you develop the judgment needed to properly apply theories and analysis to the evaluation of soils and foundation design